Answer:
All trigonometric ratios.
Step-by-step explanation:
We have to find all the trigonometric ratios.
Given:
[tex]\theta = \dfrac{4\pi}{3} = \pi + \dfrac{\pi}{3}[/tex]
Formula:
[tex]\sin(\pi +x) = -\sin(x)\\\cos(\pi +x) = -\cos(x)[/tex]
[tex]\sin(\pi + \dfrac{\pi}{3}) = -\sin(\dfrac{\pi}{3}) = -\dfrac{\sqrt{3}}{2}[/tex]
[tex]\cos ((\pi + \dfrac{\pi}{3})) = -\cos(\dfrac{\pi}{3}) = -\dfrac{1}{2}[/tex]
Formula:
[tex]\tan\theta =\dfrac{\sin\theta}{\cos\theta}\\\cot\theta = \dfrac{1}{\tan\theta}\\\sec\theta = \dfrac{1}{\cos\theta}\\\csc\theta = \dfrac{1}{\sin\theta}[/tex]
[tex]\tan(\pi + \dfrac{\pi}{3})= \dfrac{\sin(\pi + \dfrac{\pi}{3})}{\cos(\pi + \dfrac{\pi}{3})}\\\\\tan(\pi + \dfrac{\pi}{3}) = \dfrac{\frac{-\sqrt{3}}{2}}{\frac{-1}{2}} = \sqrt{3}[/tex]
[tex]\cot(\pi + \dfrac{\pi}{3}) = \dfrac{1}{\tan(\pi + \dfrac{\pi}{3})} = \dfrac{1}{\sqrt{3}}[/tex]
[tex]\sec(\pi + \dfrac{\pi}{3}) = \dfrac{1}{\cos(\pi + \dfrac{\pi}{3})} = -2[/tex]
[tex]\csc(\pi + \dfrac{\pi}{3}) = \dfrac{1}{\sin(\pi + \dfrac{\pi}{3})} = -\dfrac{2}{\sqrt{3}}[/tex]